OPTIMIZATION OF STATE-OWNED PROPERTY (BMN) FUNCTIONS THROUGH SUKUK AS A NATIONAL FINANCING INSTRUMENT - Rosyidah, Norma (Universitas Airlangga, 2015)
This study analyzes the optimization of BMN used as basis for the issuance of sukuk. The amount of assets BMN are still not up and not yet recorded an obstacle little realization of sukuk issued by the government. With the growing of covering BMN assets that are then used as SBSN's asset, it can be utilized optimally. Assets that were previously idle and neglected, finally can have economic value and maintained condition. This research uses descriptive method, where data is used is an increasing number of BMN sukuk issuance and realization of 2008-2013. Keyword : BMN, Sukuk